Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.4049/jimmunol.1203464
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death Triggered by Yersinia enterocolitica Identifies Processing of the Proinflammatory Signal Adapter MyD88 as a General Event in the Execution of Apoptosis

Abstract: Many pathogenic microorganisms have evolved tactics to modulate host cell death or survival pathways for establishing infection. The enteropathogenic bacterium Yersinia enterocolitica deactivates TLR-induced signaling pathways, which triggers apoptosis in macrophages. In this article, we show that Yersinia-induced apoptosis of human macrophages involves caspase-dependent cleavage of the TLR adapter protein MyD88. MyD88 was also cleaved when apoptosis was mediated by overexpression of the Toll–IL-1R domain–cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…3B). Inducing cell death is a common tactic used by bacterial pathogens for effective spread in the host, and Yersinia is not an exception [54]. It would be interesting to establish whether Yersinia promotes cell death in epithelial cells by targeting any of the identified molecules specifically.…”
Section: Resultsmentioning
confidence: 99%
“…3B). Inducing cell death is a common tactic used by bacterial pathogens for effective spread in the host, and Yersinia is not an exception [54]. It would be interesting to establish whether Yersinia promotes cell death in epithelial cells by targeting any of the identified molecules specifically.…”
Section: Resultsmentioning
confidence: 99%
“…While induction of cell death often depends on the balance between proapoptotic and prosurvival signals [68], the exact signaling networks that induce cell survival or cell death after engagement of TLRs are not yet completely understood [69]. There is increasing evidence that the strength, timing, and duration of TLR signaling can significantly modulate downstream outcomes [70], just as previously observed for T-cell receptor signaling [71,72], and more recently for B-cell receptor signaling [73].…”
Section: Discussionmentioning
confidence: 97%
“…10 Of note, Yersinia enterocolitica is able to deactivate TLR-induced signaling pathways, by cleaving Myd88, triggering apoptosis in macrophages. 11 This mechanism may increase Yersinia virulence in immunocompetent hosts also. In a recent article by von Bernuth et al, 12 MyD88-deficient mice were found to be susceptible to almost nearly all the microbes tested, including bacteria, viruses, protozoa, and fungi, highlighting the importance of TLR in the immune response to different pathogens.…”
Section: Targeted Next-generation Sequencing Revealed Myd88 Deficiencmentioning
confidence: 99%